1992
DOI: 10.1002/ana.410310408
|View full text |Cite
|
Sign up to set email alerts
|

MELAS: Clinical features, biochemistry, and molecular genetics

Abstract: We studied 23 patients with clinically defined mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS), 25 oligosymptomatic or asymptomatic maternal relatives, and 50 mitochondrial disease control subjects for the presence of a previously reported heteroplasmic point mutation at nt 3,243 in the transfer RNA(Leu(UUR)) gene of mitochondrial DNA. We found a high concordance between clinical diagnosis of MELAS and transfer RNA(Leu(UUR)) mutation, which was present in 21 of the 23 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
263
3
8

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(283 citation statements)
references
References 15 publications
9
263
3
8
Order By: Relevance
“…18,19 In contrast, when studying the A3243G mutation in a 24 week old foetus, there was almost no differences in the heteroplasmy level between different tissues. 20 These observations indicate that the level of heteroplasmy increases in post mitotic tissue and/ or decreases in mitotic tissue.…”
Section: Discussionmentioning
confidence: 85%
“…18,19 In contrast, when studying the A3243G mutation in a 24 week old foetus, there was almost no differences in the heteroplasmy level between different tissues. 20 These observations indicate that the level of heteroplasmy increases in post mitotic tissue and/ or decreases in mitotic tissue.…”
Section: Discussionmentioning
confidence: 85%
“…Several types of respiratory complex defects caused by m.3243 A>G have been previously reported. Ciafaloni et al reported that the mutation resulted in a decrease in the activities of complexes I + III, II + III, and IV in the muscles (Ciafaloni et al, 1992). In a previous study, we observed that deficiencies in complex I or IV were common; however, deficiencies in complex III were not observed in patients displaying the m.3243 A>G mutation (Ma et al, 2013).…”
Section: Discussionmentioning
confidence: 54%
“…It should be noted that the MELAS mtDNAmutation may cause clinical symptoms other than MELAS (14,15). In fact, the patient had no stroke-like episodes.…”
Section: Discussionmentioning
confidence: 82%